2012
DOI: 10.1016/j.freeradbiomed.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

A high-selenium diet induces insulin resistance in gestating rats and their offspring

Abstract: Although supranutrition of selenium (Se) is considered a promising anti-cancer strategy, recent human studies have shown an intriguing association between high body Se status and diabetic risk. This study was done to determine if a prolonged high intake of dietary Se actually induced gestational diabetes in rat dams and insulin resistance in their offspring. Forty-five 67-day-old female Wistar rats (n=15/diet) were fed a Se-deficient (0.01 mg/kg) corn–soy basal diet (BD) or BD+Se (as Se-yeast) at 0.3 or 3.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 72 publications
6
83
0
1
Order By: Relevance
“…In accordance with these observations, the results of several clinical trials that investigated the chemopreventive effects of dietary Se supplementation revealed that increased intake of Se above the nutrient requirements may raise the risk of type 2 diabetes mellitus in humans (222,327). Although the exact mechanism of the diabetogenic effect of high Se intake remains unclear, increased expression of GPx1, SelP, MsrB1, and SelS has been implicated in the development of type 2 diabetes and insulin resistance (198,256,287,382). At least some of these effects could be attributed to diminished intracellular H 2 O 2 levels as a result of high GPx1 activity leading to suppression of insulin signaling and increased insulin secretion, similar to GPx1-overexpressing mice (386).…”
Section: Selenoprotein Functionmentioning
confidence: 72%
“…In accordance with these observations, the results of several clinical trials that investigated the chemopreventive effects of dietary Se supplementation revealed that increased intake of Se above the nutrient requirements may raise the risk of type 2 diabetes mellitus in humans (222,327). Although the exact mechanism of the diabetogenic effect of high Se intake remains unclear, increased expression of GPx1, SelP, MsrB1, and SelS has been implicated in the development of type 2 diabetes and insulin resistance (198,256,287,382). At least some of these effects could be attributed to diminished intracellular H 2 O 2 levels as a result of high GPx1 activity leading to suppression of insulin signaling and increased insulin secretion, similar to GPx1-overexpressing mice (386).…”
Section: Selenoprotein Functionmentioning
confidence: 72%
“…Whole-blood samples of individual pigs were collected at week 0 and then biweekly after overnight food deprivation (8 h) to prepare plasma samples as previously described (3). Plasma concentrations of total TGs, total cholesterol (TC), nonesterified fatty acids (NEFAs), glucose, and insulin (at weeks 6 and 11) were analyzed as previously described (9).…”
Section: Methodsmentioning
confidence: 99%
“…Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19). However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…GPx and TR are anti-oxidant enzymes and their activities are significantly increased in mice or rats fed high supplemental level of selenium containing diet compared with mice or rats fed normal level of selenium containing diet. [33][34][35] Recently, it was reported that increasing GPx and TR activities alter the immune response toward a Th1 phenotype. 36) SelS is also considered to regulate the immune response and redox balance.…”
Section: Discussionmentioning
confidence: 99%